2015
DOI: 10.1016/j.metabol.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of leptin: energy homeostasis, neuroendocrine function and metabolism

Abstract: Leptin is secreted by adipose tissue and regulates energy homeostasis, neuroendocrine function, metabolism, immune function and other systems through its effects on the central nervous system and peripheral tissues. Leptin administration has been shown to restore metabolic and neuroendocrine abnormalities in individuals with leptin-deficient states, including hypothalamic amenorrhea and lipoatrophy. In contrast, obese individuals are resistant to leptin. Recombinant leptin is beneficial in patients with congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
427
1
47

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(484 citation statements)
references
References 176 publications
9
427
1
47
Order By: Relevance
“…This is an adaptive response driven by the hypothalamus that includes behavioral as well as metabolic modifications, such as increased sleep, diminished motor activity, and core temperature (1). During fasting, the hormonal milieu is dominated by low levels of insulin and thyroid hormones, which has been proposed as an explanation for the slowdown in weight loss after a few days of caloric restriction (2,3).…”
mentioning
confidence: 99%
“…This is an adaptive response driven by the hypothalamus that includes behavioral as well as metabolic modifications, such as increased sleep, diminished motor activity, and core temperature (1). During fasting, the hormonal milieu is dominated by low levels of insulin and thyroid hormones, which has been proposed as an explanation for the slowdown in weight loss after a few days of caloric restriction (2,3).…”
mentioning
confidence: 99%
“…When energy imbalance occurs, excessive calories accumulate as triglycerides in adipose tissue, leading to overweight and obesity. Hence, a better understanding of the energy homeostasis in a human body holds the key to finding the exact causes of obesity (Paspala et al, 2012;Szczesna et al, 2013;Chopra et al, 2014;Pan et al, 2014;Crujeiras et al, 2015;Park & Ahima, 2015;Sáinz et al, 2015).…”
Section: Energy Homeostasis and Leptin Deficiencymentioning
confidence: 99%
“…However, in recent years researchers have demonstrated that a multi-therapy of leptin in combination with other leptin sensitisers may be able to improve peripheral leptin sensitivity and may hold therapeutic promise (Moon et al, 2011;Müller et al, 2012;Matthias, 2014;Crujeiras et al, 2015;Park & Ahima, 2015). These leptin sensitisers target distinct neuroendocrine systems related to leptin signalling pathology.…”
Section: Multi-therapy Of Leptinmentioning
confidence: 99%
See 1 more Smart Citation
“…It widely recognized that adipose tissue, in addition to being a primary storage of energy, plays a very important role in body metabolism primarily through adipocyte-macrophage interaction, releasing adiponectin, FA and the hormone leptin [80][81][82]. With only about 10% total systemic glucose uptake, adipose tissue may play only a minor quantitative role in postprandial glucose metabolism.…”
Section: Adipose Tissuementioning
confidence: 99%